Mosses are Important for Soil Carbon Sequestration in Forested Peatlands - Kasimir, Å.; He, H.; Jansson, P.-E.; Lohila, A.; Minkkinen, K. (Frontiers in Environmental Science, 2021)
Nutrient-rich peat soils have previously been demonstrated to lose carbon despite higher photosynthesis and litter production compared to nutrient-poor soils, where instead carbon accumulates. To understand this phenomenon, we used a process-oriented model (CoupModel) calibrated on data from two closely located drained peat soil sites in boreal forests in Finland, Kalevansuo and Lettosuo. Uncertainty-based calibrations were made using eddy-covariance data (hourly values of net ecosystem exchange) and tree growth data. The model design used two forest scenarios on drained peat soil, one nutrient-poor with dense moss cover and a nutrient-rich with sparse moss cover. Three vegetation layers were assumed: conifer trees, other vascular plants, and a bottom layer with mosses. Adding a moss layer was a new approach, because moss has a modified physiology compared to vascular plants. The soil was described by three separate soil organic carbon (SOC) pools consisting of vascular plants and moss litter origin and decomposed organic matter. Over 10 years, the model demonstrated a similar photosynthesis rate for the two scenarios, 903 and 1034 g C m-2 yr-1, respectively, despite the different vegetation distribution. However, higher biomass accumulation was displayed for the nutrient-rich scenario which had more trees. Moss biomass did not increase but produced high litter inputs with low turnover rates compared with litter from vascular plants. The model calibration showed that decomposition rate coefficients for the three SOC pools were similar for the two scenarios, but the high quantity of moss litter input with low decomposability for the nutrient poor scenario explained the major difference in the soil carbon balance. Vascular plant litter declined with time, while SOC pools originating from mosses accumulated with time. Large differences between the scenarios were obtained during dry spells where soil heterotrophic respiration doubled for the nutrient-rich scenario, where vascular plants dominated, owing to a larger water depletion by roots. Where moss vegetation dominated, the heterotrophic respiration increased by only 50% during this dry period. We suggest moss vegetation is key for carbon accumulation in the poor soil, adding large litter quantities with a resistant quality and less water depletion than vascular plants during dry conditions.